A family‐focused intervention for heart failure self‐care: conceptual underpinnings of a culturally appropriate intervention. (13th September 2015) - Deek, Hiba; Noureddine, Samar; Newton, Phillip J.; Inglis, Sally C.; MacDonald, Peter S.; Davidson, Patricia M.
Abstract: Aim: A discussion of the conceptual elements of an intervention tailored to the needs of Lebanese families. Background: The role of informal caregiving is strongly recommended for individuals with chronic conditions including heart failure. Although this importance is recognized, conceptual and theoretical underpinnings are not well elucidated nor are methods of intervention implementation. Design: Discussion paper on the conceptual underpinning of the FAMILY model. Methods and data sources: This intervention was undertaken using linked methods: (1) Appraisal of theoretical model; (2) review of systematic reviews on educational interventions promoting self‐management in chronic conditions in four databases with no year limit; (3) socio‐cultural context identification from selected papers; (4) expert consultation using consensus methods; and (5) model development. Results: Theories on self‐care and behavioural change, eighteen systematic reviews on educational interventions and selected papers identifying sociocultural elements along with expert opinion were used to guide the development of The FAMILY Intervention Heart Failure Model. Theory and practice driven concepts identified include: behavioural change, linkage, partnership and self‐regulation. Implications for nursing: Heart failure is a common condition often requiring in‐hospital and home‐based care. Educational interventions targeting the socio‐cultural influences of the patients and their family caregivers through a structured and well‐designed program can improve outcomes. Conclusion: As the burden of chronic diseases increases globally, particularly in emerging economies, developing models of intervention that are appropriate to both the individual and the socio‐cultural context are necessary.